THE TRIPLE WIN: HOW GREEN TOURISM MARKETING BENEFITS BUSINESS, PEOPLE AND THE PLANET - Gegung, Eunike M. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The rapid growth of the tourism industry has intensified environmental degradation and sociocultural pressures, highlighting the need for more sustainable development models. This study examines the role of green tourism marketing as a strategic mechanism to achieve a “triple win” for businesses, communities, and the environment. Using a qualitative approach based on an extensive review of academic literature, policy documents, and selected case studies, the research explores how sustainability-oriented marketing practices enhance business competitiveness, support community well-being, and promote environmental conservation. The findings suggest that authentic and transparent green marketing enhances brand differentiation, promotes consumer trust, and promotes responsible travel behavior. Moreover, when aligned with genuine sustainable practices, green tourism marketing contributes to local empowerment, cultural preservation, and the protection of biodiversity. The study concludes that green tourism marketing is not merely a promotional tool but a critical driver for integrating economic performance with social and environmental responsibility in the tourism sector.